Harnessing local wisdom: A cornerstone for rural tourism development - Dafinka Mucunska; Mijalce Gjorgievski (UTMS Journal of Economics, 2023)
In recent decades, tourism has evolved into one of the largest, fastest-growing, and most dynamic industrial sectors, encompassing various complementary businesses across diverse fields. The pivotal role of local knowledge in shaping tourism services and products in rural areas cannot be overstated. This paper explores the central theme: "The Essential Role of Local Knowledge in Planning, Management, and Implementation of Tourism Processes for the Sustainable Development of the Maleshevo Region". Employing a qualitative approach with ethnography as the methodology, this research aims to underscore how the inhabitants of this region, owing to unique geographical circumstances and physical 'isolation' resulting from challenging transportation and communication channels, have cultivated an indigenous tradition and culture. This cultural heritage, largely preserved to this day, represents a valuable asset from a tourist perspective, offering a rich source for the creation of both existing and novel attractive tourist products and services. These, in turn, serve as the foundation and a unique opportunity for the continued sustainable growth of the area.
Keywords: L83; Z32; I15; O18; 330; tourism; local knowledge; rural area; sustainable growth